Analisis Gaya Kepemimpinan Pemerintah dalam Penanggulangan Bencana Studi Kasus di Indonesia - Fadhilah, Raihan; Saepudin, Eli Apud; Alfiah, Ovi; Prasya, Sakti Dwiantoro; Syahid, Muhammad (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to analyze the Indonesian government's leadership style in disaster management efforts. Indonesia is a country that is often affected by natural disasters. The success in disaster management is greatly influenced by the government's leadership style that involves planning, coordination, and collaboration with various parties. Findings from the study show that responsive, adaptive, and collaborative leadership styles play a significant role in accelerating the process of evacuation, aid distribution, and post-disaster relief. Some challenges are still faced, such as limited resources, bureaucracy and suboptimal cross-sector coordination. This study concludes that to achieve effective leadership in the field of disaster management, a combination of decisiveness, flexibility, and solid cooperation with various related parties is required.